Timeliness of Financial Reporting: The Effect of Profitability, Financial Distress and Operational Complexity Moderated by Firm Size - Melati Pramudita Lestari; Desty Wana; Susan Andriana (Pusat P2M Politeknik Negeri Batam, 2024)
Timely financial reporting is a widespread challenge, affecting numerous publicly traded companies in Indonesia. An examination of data from the Indonesia Stock Exchange (IDX) website, spanning the years 2010 to 2020, reveals that many companies submitted their financial reports past the deadline. The number of late submissions fluctuated over this period, with a noticeable decrease in 2010-2012 and 2016, followed by significant increases in 2013-2015 and 2018-2020. The year 2020 saw the highest number of late filers (96 companies), followed by 2015 (63 companies). This research delves into the elements that impact how quickly manufacturing companies listed on the Indonesia Stock Exchange (IDX) release their financial reports. This research investigates the influence of several factors on the promptness of corporate reporting. Specifically, it examines how a company's profitability, financial distress, and the intricacy of its business operations impact the timeliness of its reporting. It also considers whether the size of a company influences these relationships. This study employs a quantitative approach, utilizing panel data regression and moderated regression analysis (MRA) with EViews 10 software to examine associations within the data. The results showed that profitability and complexity have a negative effect on the timeliness of financial reporting, while financial distress has a positive effect. Firm Size can moderate the effect of profitability on the timeliness of financial reporting. However, it cannot moderate the effect of financial distress and operating complexity on the timeliness of financial reporting.